PELATIHAN PEMBUATAN WEBSITE PEMASARAN PRODUK DI YAYASAN PESANTREN AS-SYARIF GOWA KELURAHAN PANGKABINANGA KECAMATAN PALLANGGA KABUPATEN GOWA - Andi Sawe Ri Esso; Muhammad Kusnady Tabsir; Soemarno Hidayatullah; Rizka Rayhana (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
This training aims to empower students and teachers at the As-syarif Education Foundation in terms of the use of digital technology, especially the creation of product marketing websites. Yayasan Pendidikan As-syarif is an educational entity that is committed to providing quality education in teaching memorization of the Qur'an, for its students, while their education students are equipped with knowledge on how to promote the products produced by their community. However, the lack of online representation and the lack of technical expertise in website creation have been obstacles in achieving these goals. This training will provide comprehensive material on the basic concepts of website creation, choosing the right platform, attractive design, to increase online visibility. The practicum session will allow participants to directly implement the knowledge gained and create a marketing website for